2006
DOI: 10.1097/01.ta.0000217270.16860.32
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Need for Early Tracheostomy: A Multifactorial Analysis of 992 Intubated Trauma Patients

Abstract: Discrete risk factors predict the need for tracheostomy for trauma patients. We recommend that patients with >or=90% risk undergo early tracheostomy and that it is considered in the >or=80% risk group to potentially decreased morbidity, increased patient comfort, and optimize resource utilization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
55
1
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(67 citation statements)
references
References 21 publications
9
55
1
2
Order By: Relevance
“…Patients with C-SCI are at increased risk of respiratory failure that may lead to the need for tracheostomy [6,11,13,15,21]. Pulmonary complications are the most common complications in patients with C-SCI [7,9].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients with C-SCI are at increased risk of respiratory failure that may lead to the need for tracheostomy [6,11,13,15,21]. Pulmonary complications are the most common complications in patients with C-SCI [7,9].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with respiratory failure after C-SCI will require intubation and mechanical ventilation, leading to tracheostomy. It has been reported that 21-77 % of patients with C-SCI have undergone tracheostomy [6,11,13,15,21].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations